EXPLORING LEARNERS’ ATTITUDE TOWARD ENGLISH LEARNING INDIGITAL ERA(Study In English Department at state university of Gorontalo) - Djihan Said Subetan; Harto Malik, Rahmawaty Mamu (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The use of technology has transformed how students learn English, especially in the digital era. Understanding students' attitudes toward this shift is essential for enhancing their learning outcomes. This study examines the attitudes of fourth- semester English Department students at Gorontalo State University, focusing on cognitive, affective, and behavioral aspects. A quantitative approach was applied by distributing close-ended questionnaires online using Google Forms. The data were analyzed based on the Three Component Attitude Model. The results show that students generally have a positive attitude toward English learning supported by technology. The cognitive aspect achieved the highest score (86%), highlighting students’ belief in the benefits of English for career opportunities and global communication. Meanwhile, the behavioral aspect also showed active participation in using digital platforms (79%). However, the affective aspect scored lower (73%), reflecting mixed feelings about the use of technology in learning. These findings suggest that while students are open to using technology, further efforts are needed to address emotional barriers and optimize engagement. Educators are encouraged to incorporate digital tools creatively to foster a more effective and enjoyable learning experience.